Women as a driver to address gaps in the global surgical workforce - Isabella Busa; Shobhana Nagraj (BMC, 2023)
Abstract Five billion people around the world lack access to safe and affordable surgical, anaesthetic, and obstetric care. There is a link between countries in which women are underrepresented in the surgical workforce and those struggling to meet their surgical need. In this commentary article, the underrepresentation of women in low- and middle-income country's (LMIC) surgical workforce is discussed. It is argued that the issue is self-reinforcing. On one hand, active change requires a sufficient number of female surgeons to initiate it. On the other, women can only start to penetrate the surgical workforce once they are safe, healthy, and motivated enough to do so, in turn depending on the presence of female surgeons to advocate for their female patients and empower future generations of young girls and women.